Gender and Labour Market Adjustment to Trade: The Case of India - Louise Johannesson; Hildegunn Kyvik Nordås (Research Institute of Industrial Economics (IFN), 2020)
Standing at 24% in 2018, India's female labour force participation is only half of the global average (48%). At the same time, India has one of the widest gender wage gaps in the world and women are less likely to be employed in the formal sector compared to men. This study focuses on the role of international trade as a source of increased competitive pressure in domestic markets, and how it affects relative wages and formal employment between men and women. Using the Revealed Symmetrical Comparative Advantage index, sectors of comparative advantage and disadvantage are identified and matched on Indian labour force surveys that contain information on sectoral employment and earnings. We find that sectors of comparative advantage in services have the lowest gender wage gap, with women earning 24% less than their male counterpart, while women in manufacturing earned on average 40% less than male workers. The Oaxaca-Blinder decomposition shows that the total gender wage gap in sectors of comparative advantage in services are minor while it is quite substantial in manufacturing, regardless of the comparative advantage. The study concludes that trade goes hand in hand with a smaller gender wage gap in the services sectors as it allows women to leverage their skills better than in manufacturing.
Keywords: F14; F16; 330; Gender; International trade; Jobs; Earnings